THE USAGE OF YOUTUBE FOR VOCABULARY TEACHING TO ENHANCE SELF-STUDY DURING THE PANDEMIC. - Abuova, Janar (Журнал иностранных языков и лингвистики, 2021)
The aim of the paper to present the main reasons for YouTube implementation for online classes in a higher educational institute. It was found that short new and interesting videos with subtitles might increase self-study in students and facilitate their vocabulary learning. By assigning videos as homework and creating meaningful tasks teachers help students to stay focused during the lesson and be even more motivated during the self-study. The usage of subtitles both in native and target language not only increase language learning but also present the high level of cognitive thinking which proves that the percentage of learned vocabulary is going to be much higher.